Total Knee Replacement in Shree Birendra Hospital: An Early Experience - Chand, Pankaj; Magar, Sushil Rana; Thapa, Bishnu Babu; Shah, Rajesh Pratap; Shrestha, B; Manandhar, Rajeev Raj (Nepal Orthopaedic Association Journal, 2016)
INTRODUCTION: Total knee replacement is established as one of the most successful surgical procedure for relief of pain and restoration of function in arthritic knees. Total knee replacement is done routinely in very few centers in Nepal and only few outcome studies have been published. The aim of this paper is to present the outcome of total knee replacement done in Shree Birendra Hospital over a period of three and a half years. METHODS: Sixteen total knee replacements which were carried out in Shree Birendra Hospital of Kathmandu between May 2011 and December 2014 were included in the study. Cemented fixed bearing implant PFC Sigma (Depuy,USA) were used in all cases. Postoperative rehabilitation protocol of our institute was followed. Patients were reviewed at 6 weeks, 12 weeks, 6 months, one year and annually then onwards. Outcome in terms of Knee Society Score as well as Knee Society Functional Score were measured. RESULTS: A total of 16 total knee replacements were performed on 14 patients. There were two bilateral total knee replacements and 12 were unilateral knee replacements. The mean age of the patients was 59.3 years (range 45-75 years). The commonest reason for knee replacement was primary osteoarthritis. The average follow up period was 34 months (range 24 to 47 months). There was no post-operative infection. One patient developed a patellar clunk. Post operatively both the Knee Society Score (KSS) as well as Knee Society Functional Score (KSFC) showed statistically significant improvements. CONCLUSIONS: Total knee replacement provides significant relief of pain and improvement of function in advanced stage arthritis of knee.